The DYNAMICS OF INFLATION, INTEREST RATES, AND RETURN ON ASSETS (ROA) ON STOCK PRICES IN THE BASIC CHEMICAL INDUSTRY SECTOR (2021-2024) - Dwi Danesty Deccasari (Politeknik Negeri Ambon, 2026)
Introduction: This study examines the effect of Return on Assets (ROA), Interest Rates, and Inflation on Stock Prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The objective is to identify key predictors of stock prices to support investment decisions. Methods: Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to secondary financial report data, which is suitable for analyzing complex relationships with limited samples. Results: ROA has a positive and significant effect on stock prices (β = 0.512, p < 0.05), indicating that strong financial performance drives stock price appreciation. Interest Rates have a negative and significant impact, while Inflation is insignificant, indicating that this macroeconomic factor is less dominant. ROA is the strongest predictor, followed by Interest Rates. In conclusion, internal profitability is more crucial than external conditions such as inflation. Suggestion: Investors prioritize high ROA; management should improve asset efficiency. Keywords: Inflation, Interest, Return On Assets